Pengaruh Kombinasi Pengencer Semen Life dan Tris Modifikasi Terhadap Kualitas Spermatozoa Babi Landrace - Keta, Katarina Miranda; Kune, Petrus (Journal of Comprehensive Science, 2024)
Artificial insemination (IB) is one of the reproductive technologies that has been widely used to increase the population and production of livestock, including pigs, both qualitatively and quantitatively. The success of the IB program depends not only on the quality of the semen of the studs, but also on the ability to maintain the quality of the semen as well as increase the volume through dilution. Semen dilution aims to reduce the density of spermatozoa and extend their lifespan, so that more females can be inseminated. Tris thinners are often used because of their citric acid and fructose content which help maintain pH stability as well as protect spermatozoa. In addition, life cement diluent is also used because of its ability to maintain the survival of spermatozoa. The addition of egg yolks and natural antioxidants, such as moringa leaf extract, is expected to fight free radicals and improve semen quality for IB. This study aims to determine the effect of the combination of semen life and modified tris on the quality of landrace pig spermatozoa. This study used a complete randomized design (CRD) method with 5 treatments and 5 replicates. Each treatment consisted of P0: 100% life semen+1% EDK, P1: 75% life semen+25% tris+1% EDK, P2: 50% life semen+50% tris+1% EDK, P3: 25% life semen+75%tris+1%EDK, P4: 100% tris+1% EDK. The cattle used were 2-3 years old, and the spermatozoa used were taken manually by grasping the penis using a cleaned hand. The results of this study showed that the P4 treatment had a significant effect (P<0.05) compared to the other treatments, with motility values of 45.80±3.49%, viability of 56.36±2.06%, abnormality of 5.00±0.86%, and survival of 44.39±2.53 hours. It can be concluded that 100% Tris diluent + 1% EDK is more effective in maintaining the viability of landrace pig spermatozoa for 40 hours of storage time.